Study for the in-situ and on-site implementation of the combined physical, chemical and biological method for the decontamination of areas impacted by oil spills - Ledesma Sarmiento, Giovany Eduardo (2016)
This research explains the effectiveness of the on-site implementation of a combination of physical, chemical and biological techniques for restoration of ecosystems affected by oil spills at national and international level, by means of optimizing resources such as cost and time, compatibility and affinity of the restoration method with the environment by using biodegradable dispersants, selective logging of plant species, soil reshaping and reforestation of the area restored with native seedlings. The implementation of this on-site combined method in an ecosystem impacted by oil spill in the northeast region of Peru resulted in a high efficacy percentage of ecosystem restoration, therefore it is highly recommended for application in the restoration of ecosystems affected by oil spills, as long as the requirements defined for the process critical variables are adjusted.